Factors associated with anemia in gestation in Huánuco, 2018 - Cisneros-Rojas, Erick P. (2019)
Objective. To determine the association between the level of knowledge of anemia, nutritional status, socioeconomic status and anemia in pregnant women who have been treated in health facilities belonging to the Huánuco Network in 2018. Methods. An observational, analytical, cross-sectional, multicentric study of pregnant women attended in 3 facilities belonging to the Huánuco network was conducted during the last 3 months of 2018. Data analysis was performed using the IBM SSPSS version 23, to determine the associations between anemia and independent variables (level of knowledge, nutritional status and socio-economic cultural level) Results. Two hundred and seventy eight participants were evaluated. It was found that women surveyed 38.80% have some kind of higher education, and 1.40% of women who did not have any instruction. The 80.60% are of urban origin and only 9.70% perceive income above the minimum vital remuneration, in addition, we find a prevalence of 19.40% of anemia. An association was found between anemia and socioeconomic level (p = 0.016, 95% CI) where the majority of those suffering from anemia had a categorization below the mean (16.90%). The relationship between anemia and level of knowledge was significant (p = 0.000, 95% CI) being that 11.50% had anemia and an inadequate level of knowledge. Conclusions. Gestational anemia in Huánuco is associated with the level of knowledge, socioeconomic and cultural level.